Hydroxysafflor Yellow A Suppresses MRC-5 Cell Activation Induced by TGF-β1 by Blocking TGF-β1 Binding to TβRII - Pan, Ruiyan; Zhang, Yadan; Zheng, Meng; Zang, Baoxia; Jin, Ming (Frontiers in Pharmacology, 2017)
Abstract Hydroxysafflor yellow A (HSYA) is an active ingredient of Carthamus tinctorius L.. This study aimed to evaluate the effects of HSYA on transforming growth factor-β1 (TGF-β1)-induced changes in proliferation, migration, differentiation, and extracellular matrix (ECM) synthesis and degradation in human fetal lung fibroblasts (MRC-5), to explore the mechanisms whereby HSYA may alleviate pulmonary fibrosis. MRC-5 cells were incubated with various doses of HSYA and/or the TGF-β receptor type I kinase inhibitor SB431542 and then stimulated with TGF-β1. Cell proliferation was measured by 3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfo-phenyl)-2H-tetrazolium inner salt assay. Cell migration was detected by wound-healing assay. Protein levels of α-smooth muscle actin (α-SMA), collagen I α 1 (COL1A1), and fibronectin (FN) were measured by immunofluorescence. Protein levels of matrix metalloproteinase-2, tissue inhibitor of matrix metalloproteinase-1, tissue inhibitor of matrix metalloproteinase-2, TGF-β type II receptor (TβRII), and TGF-β type I receptor were detected by western blotting. TβRII knockdown with siRNA interfered with the inhibitory effect of HSYA on α-SMA, COL1A1, and FN expression, and TGF-β1-induced Sma and Mad protein (Smad), and extracellular signal-regulated kinase/mitogen-activated protein kinase signaling pathway activation. The antagonistic effect of HSYA on the binding of fluorescein isothiocyanate-TGF-β1 to MRC-5 cell cytoplasmic receptors was measured by flow cytometry. HSYA significantly suppressed TGF-β1-induced cell proliferation, migration, and expression of α-SMA, COL1A1, and FN by targeting TβRII in MRC-5 cells. These findings suggest that TβRII is the target responsible for the inhibitory effects of HSYA on TGF-β1-induced pathological changes in pulmonary fibrosis.